Obesity and Pancreatic Cancer: Overview of Epidemiology and Potential Prevention by Weight Loss. Issue 2 (February 2018) - Xu, Mu; Jung, Xiaoman; Hines, O. Joe; Eibl, Guido; Chen, Yijun
Abstract : Abstract: Currently, there are no effective preventive strategies for pancreatic cancer. Obesity has been increasingly recognized as a strong but modifiable risk factor of pancreatic cancer. In this article, we aim to review the literature regarding weight loss on prevention of pancreatic cancer. Epidemiological and laboratory studies have shown that obesity is associated with increased incidence of pancreatic cancer and potentially worse cancer outcome. Whereas the underlying pathomechanisms remain unclear, chronic inflammation, insulin resistance, and altered intestinal microbiota are all implicated in the carcinogenic effect of obesity. Weight loss, especially the durable and significant weight loss after bariatric surgery, has been shown to reduce the risks of multiple cancers and may become a good intervention for pancreatic cancer prevention.